2017
DOI: 10.1186/s12887-017-0967-9
|View full text |Cite
|
Sign up to set email alerts
|

Why gone too soon? Examining social determinants of neonatal deaths in northwest Ethiopia using the three delay model approach

Abstract: BackgroundWithout improving the survival of newborns, meaningful reduction in under-five mortality is difficult. Most neonatal deaths are preventable when appropriate and timely care is sought. In Ethiopia, there is lack of evidence on the type and contribution of delays in treatment seeking to neonatal deaths.MethodsA community based social autopsy (SA) of 39 neonatal deaths was conducted from March 16 to 24, 2016 in Dabat Health and Demographic Surveillance System (HDSS) in northwest Ethiopia. The result was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 17 publications
2
30
1
Order By: Relevance
“…Another study conducted across Nigeria, Tanzania and Ethiopia finds fathers act as authoritative figures of whom agreeance is needed to follow through with accessing treatment methods, even though these figures may not often directly involve themselves in newborn care [26]. As timing of care is an essential component of ameliorating health conditions and preventing neonatal death [17,27], increasing paternal awareness of neonatal danger signs through acceptable campaign messaging may facilitate transition from illness recognition to facility access.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study conducted across Nigeria, Tanzania and Ethiopia finds fathers act as authoritative figures of whom agreeance is needed to follow through with accessing treatment methods, even though these figures may not often directly involve themselves in newborn care [26]. As timing of care is an essential component of ameliorating health conditions and preventing neonatal death [17,27], increasing paternal awareness of neonatal danger signs through acceptable campaign messaging may facilitate transition from illness recognition to facility access.…”
Section: Discussionmentioning
confidence: 99%
“…Although HEWs may refer those seen during home visits or at health posts to higher facilities for care, significant barriers limit community members in accepting these referrals. Sociocultural factors preventing care at health facilities include differences in gender-based priorities and decision-making dynamics at the household level which may delay seeking care for sick neonates [15][16][17]. Barriers impeding demand of care for newborn treatments include fear of newborn exposure to environmental factors (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The three‐delays model was developed in 1994 to better characterize factors that contribute to maternal mortality (Figure1) . Since then, the model has been applied to multiple other clinical situations where social and economic factors significantly influence clinical outcomes . The model proposes that delays in care can be classified into three main categories: delays in (i) seeking care, (ii) reaching care, or (iii) receiving care.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, delay in treatment-seeking outside home was associated with 81% of newborn deaths [27]. The current trial did not have effect on early referral of newborns; however study data not reported in the tables above indicated that having a means of transportation, e.g., motorcycle, car, did increase likelihood of bringing a sick infant to an appropriate facility (p = 0.004).…”
Section: Discussionmentioning
confidence: 52%